KEANEKARAGAMAN JENIS POHON DI HUTAN ADAT RIMBO TUJUH DANAU DESA BULUH CINA KABUPATEN KAMPAR PROVINSI RIAU - Muthia Zilyani Putri; Defri Yoza; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research is to know the composition of tree species diversity of tree species that found in Customary Forest of RimboTujuhDanau at BuluhCina village. The method used in this research is purposive sampling method. Data analysis using the Important Value Index (IVI) and Diversity Index (H’) Shannon-Wiener. The result showed that the composition of tree species found in the Customary Forest of RimboTujuhDanau village as much as 39 types of 24 family. The most dominant is the family myrtaceae and the quantity as 6 types of vegetation. The value of diversity in the type of seedling is 2,13, stake level is 2,34, pillar level is 2,48 and tree level is 2,54. The diversity of tree species in Customary Forest of RimboTujuhDanau at each level of the growth medium with value belongs to 1≤H’<3. Keywords:Types of composition, Diversity of species, Customary Forest Of Rimbo Tujuh Danau